2008
DOI: 10.1103/physrevlett.101.096101
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and Chain Size Dependence of Near Surface Dynamics of Glassy Polymers

Abstract: We use nanohole relaxation to study the surface relaxation of films of glassy isotactic poly (methyl methacrylate) (i-PMMA) films. These measurements allow us to obtain the time dependent relaxation function at a number of different sample temperatures for the first 2-3 nm of the free surface in a system often used as a model system for the effect of the substrate on thin film dynamics. The surface is observed to relax at temperatures up to 42 K below the bulk Tg value, even on systems where the thin film Tg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
100
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 26 publications
10
100
0
Order By: Relevance
“…So far only poly(methyl methacrylate) was studied and strong deviations of surface relaxation from bulk behavior was found. Although the ion-induced deformations follow the general relaxation laws of pristine polymers, they showed an enhanced mobility, in accordance to what was found for nanoscopic volumes of deformed polymers produced by other means of surface perturbation [9,10].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…So far only poly(methyl methacrylate) was studied and strong deviations of surface relaxation from bulk behavior was found. Although the ion-induced deformations follow the general relaxation laws of pristine polymers, they showed an enhanced mobility, in accordance to what was found for nanoscopic volumes of deformed polymers produced by other means of surface perturbation [9,10].…”
Section: Introductionsupporting
confidence: 85%
“…Thus such regions are in a highly out of equilibrium state and relaxation times on glassy systems are known to depend on the deviation from equilibrium [12]. Finally, the impact features are on the surface of the targets, where the mobility of polymer chains can be significantly larger than the bulk [9,10,[12][13][14][15][16]. All the above facts may be contributing to the fast relaxation rates observed for the ion-induced deformations.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the interaction between a polymer and a solid substrate can suppress molecular relaxation in an interfacial region, leading to peculiar slower dynamics in this region. [9][10][11][12][13] Measurements of the relaxation rate using a 20-nm-thick fluorescently labeled layer that has been incorporated into polymer films have revealed that the rate of dynamics depends on the distance from both the free surface and the interface. These dynamics vary continuously, exhibiting bulk-like characteristics toward the interior layer sandwiched between the surface and the interfacial layers.…”
Section: Introductionmentioning
confidence: 99%
“…1 Therefore, several methods were proposed to monitor the dynamic of confined polymers at different length scales. [7][8][9][10][11][12][13][14][15][16][17][18][19] The segmental dynamic in freestanding PS films measured by means of dielectric relaxation was found to be faster than the bulk, which is coherent with the T g reduction. 7,8 On the other hand, the numerous methods used to probe the large scale dynamic yielded different conclusions.…”
Section: Introductionmentioning
confidence: 80%
“…This property is of great importance for several nano-technological applications such as the elaboration and stability of nanoscale polymer structures, adhesion, and environment-friendly coatings, among others. By far, thin film is the most studied nanoconfinement geometry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] compared to the other geometries: nanospheres 20-23 and nanotubes. 9 Numerous studies determined the existence of an impressive depression of the nanoconfined glass transition temperature (T g ) in supported and free-standing polystyrene (PS) thin films.…”
Section: Introductionmentioning
confidence: 99%